USING A VISUAL-CONSTRUCTIVE MODEL IN INTRODUCING SEMIOTIC EDUCATION TO PRIMARY CLASS STUDENTS - Abdusamatov Alisher Sobirovich (Scholar Express Journal, 2023)
In this article, the importance of semiotic aspects in teaching mathematics to young students, its applications, the necessary pedagogical conditions, the scientists and their views are described in detail, the branches, directions of semiotics and how we can use it in our daily life. passed
Keywords: Semiotics; primary education; mathematics